MEANS OF ORIENTEERING IN EDUCATION OF JUNIOR SCHOOLCHILDREN WITH INTELLECTUAL DISABILITY - Irina V. Mayorkina (Russian State Vocational Pedagogical University, 2015)
The purpose of this study is to examine the impact of the adapted methods of basic training in orienteering (BTIO) on the correction of physical fitness and mental development of junior schoolchildren with intellectual disability (ID).Methods. The following methods were used: theoretical analysis of literature, generalization, «forming» experiment, mathematical statistics, testing of physical qualities, psychological testing and pedagogical observation.Results and scientific novelty. The conditions of basic training in orienteering for junior schoolchildren with intellectual disability are determined wherein the correction of physical fitness and mental functions through the means of orienteering will be the most effective. Methods of basic training were substantiated and adapted for the capabilities of junior schoolchildren with ID. The author has defined the effect of orienteering exercises on the development of speed-andstrength qualities, overall endurance, movement speed, coordination; fine motor skills; stability, volume and switching of attention, volume of picturesque and verbal memory, representational thought and verbal-logical thinking; volitional qualities.The study has revealed wholesome influence of orienteering on correction of physical fitness and mental functions of schoolchildren of 9-10 years with intellectual disability.Practical significance. The results could be used for education of junior schoolchildren with ID during extra classes in special (correctional) schools of Type-7 and during remedial classes (remedial and developing teaching) in schools of general education. The results could also be applied for training of teachers of additional education. The adapted methods of BTIO for junior schoolchildren with ID could be used for normally developing children of younger age. Practical recommendations on the organization and conditions of orienteering exercises for junior schoolchildren with ID, games and intellectual exercises could also be proposed for other sports.